Indholdsfortegnelse til"Tidsskrift for Landoekonomi". 1ste, 2den og 3die Række. 1831 — 1866. - Jørgensen, B. S. (Tidsskrift for Landøkonomi, 2018)
Indholdsfortegnelse til"Tidsskrift for Landoekonomi". 1ste, 2den og 3die Række. 1831 — 1866.